Etniska hierarkier och (icke-)representation: Partikandidater med migrationsbakgrund vid svenska valet 2014 (Sociologisk Forskning, 2018)
Ethnic hierarchies and (non)representation. Party candidates with migration background in the general election of 2014.This paper analyses the extent to which individuals with migration background were appointed and elected into different levels of public decision-making bodies in the latest Swedish general election (2014). Individuals of ”migration background” refers in this study to those born abroad or born in Sweden with two foreign-born parents. Data for this study is taken from Statistics Sweden’s register of candidates elected in municipal, county and national parliamentary elections in 2014, supplemented by information from other Statistics Sweden’s registers. The results demonstrate that: (a) individuals with a migration background are severely underrepresented in the Swedish decision-making bodies; (b) even in cases when individuals with a migration background are nominated on the party lists, they have less of a chance of being elected compared to native candidates. (c) The dominant ”resource theory” cannot explain the underrepresentation of the stigmatized migrant groups and their descendants, and finally; (d) the results indicate some support to the hypothesis about the importance of access to social networks in order to be nominated and elected.
Keywords: political representation; migration background; elections; decision-making bodies